Miejski Ośrodek Kultury w Zgierzu – więcej niż kultura… - Sadowska, Monika (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
The articles focuses on the activity of the Town Cultural Centre in Zgierz. An examination of the provisions of the law allows us to rationally explain the aims and tasks faced by the Centre, and the methods due to which the Town Cultural Centre is perceived as a centre for alternative culture, a forum for social debate, and, primarily, as a people-friendly institution.